PENGARUH SELF SERVICE TECHNOLOGY TERHADAP KEPUASAN GENERASI MILENIAL PADA LAYANAN DIGITAL BANK SYARIAH DI KELURAHAN MUNJULJAYA PURWAKARTA - Eka Ahadiyat Suryana; Asep Dede Kurnia; Wilda Mahdalia (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2026)
The development of digital banking services encourages the application of Self-Service Technology (SST) to improve the efficiency and quality of services, especially in Islamic banking which is widely used by the millennial generation. However, the use of SST does not necessarily increase customer satisfaction because it is influenced by user characteristics and digital literacy levels. This study aims to analyze the influence of Self-Service Technology on the satisfaction of the millennial generation of users of Islamic banking digital services in Munjuljaya Village, Purwakarta Regency. The study used a quantitative approach with a descriptive design of 100 respondents who were selected through “simple random sampling”. Data were collected using a Likert scale questionnaire and analyzed by simple linear regression using SPSS version 26. The results of the study show that *Self-Service Technology* has a negative and significant effect on the satisfaction of the millennial generation. A determination coefficient value (R²) of 0.257 indicates that SST contributes 25.7% to customer satisfaction, while 74.3% is influenced by other factors outside the research model. These findings show that the successful implementation of self-service technology does not only depend on the use of technology, but also on the suitability of features, ease of use, and the ability of technology to meet user needs and expectations.